POLITIK HUKUM PERADILAN ELEKTRONIK DI INDONESIA (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
The Covid-19 pandemic has changed public services delivery, including in the field of judicial services. One of these changes is the possibility of the trial process being conducted electronically by mean using information and communication technology, based on the internal regulations issued by the Supreme Court. Of course, every policy has advantages and disadvantages. By reviewing these two things, continuous improvement can be made so that the vison of the Supreme Court can be achieved in the form of estbablishing the ideal judicial body. Based on this, the author then takes two formulations of the problem, namely how is the regulation of electronic justice made by the Supreme Court at this time (ius constitutum)? and how should the regulation of electronic justice be in the future (ius constituendum) so that the vision of estbablishing the ideal judicial body can be achieved? To answer the formulation of the problem, the authors conducted research using normative juridical research methods. From the results of the research that has been carried out, it is concluded that there is disharmony of various regulations related to electronic justice, there are no clear rules regarding the application of the principle of openness to the public in electronic civil proceedings and it is not possible for mediation and diversion processes to be carried out online. Therefore, there is a need for improvement of regulations related to electronic justice, either by revising existing regulations or by making new one. Keywords: Policy, Judicial Process, Electronic Litigation